SURVEY KEPADATAN LARVA AEDES AEGYPTI DI KECAMATAN MAMUJU KABUPATEN MAMUJU - Zrimurti Mappau; Siti Rahmah; Ridhayani Adiningsih (Politeknik Kesehatan Kemenkes Mamuju, 2016)
Aedes aegypti is a vector of dengue fever. Vector density may be effect of disease incidence because of the high density and highly resistant to increase of the disease. Larvae density in an area influenced by availabiloty of kontainers. The objective of this study to determine of larvae density of Aedes aegypti mosquito in endemic and non endemic area in Mamuju District based on House Index value, Kontainer Index value, Breteau Index value, and Density Figure level. We did observasional study with cross sectional by collected data and observation to larvae density of Aedes aegypti in its kontainers. Sample size determination using simple random sampling Lemeshow formula as much as 340 in endemic area and 295 in non endemic area. Based on density figure level, endemic and non endemic area included in average category so that area potential for the occurance of infection.